Temporal Envelope Changes of Compression and Speech Rate: Combined Effects on Recognition for Older Adults. - Jenstad, Lorienne M.; Souza, Pamela E. (Journal of Speech, Language & Hearing Research, 2007)
Purpose: When understanding speech in complex listening situations, older adults with hearing loss face the double challenge of cochlear hearing loss and deficits of the aging auditory system. Wide-dynamic range compression (WDRC) is used in hearing aids as remediation for the loss of audibility associated with hearing loss. WDRC processing has the additional effect of altering the acoustics of the speech signal, particularly the temporal envelope. Older listeners are negatively affected by other types of temporal distortions, but this has not been found for the distortion of WDRC processing for simple signals. The purpose of this research was to determine the circumstances under which older adults might be negatively affected by WDRC processing and what compensatory mechanisms those listeners might be using for the listening conditions when speech recognition performance is not affected. Method: Two groups of adults with mild to moderate hearing loss were tested: (a) young-old (62-74 years, n = 11) and (b) old-old (75-88 years, n = 14). The groups did not differ in hearing loss, cognition, working memory, or self-reported health status. Participants heard low-predictability sentences compressed at each of 4 compression settings. The effect of compression on the temporal envelope was quantified by the envelope difference index (EDI; T. W. Fortune, B. D. Woodruff, & D. A. Preves, 1994). The sentences were presented at three rates: (a) normal rate, (b) 50% time compressed, and (c) time restored. Results: There was no difference in performance between age groups, or any interactions involving age. There was a significant interaction between speech rate and EDI value; as the EDI value increased, representing higher amounts of temporal envelope distortion, speech recognition was significantly reduced. At the highest EDI value, this reduction was greater for the time-compressed than the normal rate condition. When time was restored to the time-compressed signals, speech recognition did not improve. Conclusion: Temporal envelope changes were detrimental to recognition of low-context speech for older listeners once a certain threshold of distortion was reached, particularly for rapid rate speech. For this sample tested, the effect was not age related within the age range tested here. The results of the time-restored condition suggested that listeners were using acoustic redundancy to compensate for the negative effects of WDRC distortion in the normal rate condition. Reprinted by permission of the publisher.